Varieties of capitalism the institutional foundations of comparative advantage - Hall, Peter A., 1950-; Soskice, David W., 1942-; Oxford eBooks (Oxford : Oxford University Press, 2001)
Applying the new economics of organisation and relational theories of the firm to the problem of understanding cross-national variation in the political economy, this volume elaborates a new understanding of the institutional differences that characterise the 'varieties of capitalism' worldwide.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Capitalism; Institutional economics; Competition, International; Comparative advantage (International trade); Electronic books